High risk bladder cancer: current management and survival - Anna M. Leliveld; Esther Bastiaannet; Benjamin H.J. Doornweerd; Michael Schaapveld; Igle J. de Jong (International Brazilian Journal of Urology, 2011)
PURPOSE: To evaluate the pattern of care in patients with high risk non muscle invasive bladder cancer (NMIBC) in the Comprehensive Cancer Center North-Netherlands (CCCN) and to assess factors associated with the choice of treatment, recurrence and progression free survival rates. MATERIALS AND METHODS: Retrospective analysis of 412 patients with newly diagnosed high risk NMIBC. Clinical, demographic and follow-up data were obtained from the CCCN Cancer Registry and a detailed medical record review. Uni and multivariate analysis was performed to identify factors related to choice of treatment and 5 year recurrence and progression free survival. RESULTS: 74/412 (18%) patients with high risk NMIBC underwent a transurethral resection (TUR) as single treatment. Adjuvant treatment after TUR was performed in 90.7% of the patients treated in teaching hospitals versus 71.8 % in non-teaching hospitals (p < 0.001). In multivariate analysis, age (60-79 years OR 0.40 and > 80 years OR 0.1 p = 0.001) and treatment in non-teaching hospitals (OR 0.25; p < 0.001) were associated with less adjuvant treatment after TUR. Tumor recurrence occurred in 191/392 (49%) and progression in 84 /392 (21.4%) patients. The mean 5-years progression free survival was 71.6% (95% CI 65.5-76.8). CONCLUSION: In this pattern of care study in high risk NMIBC, 18% of the patients were treated with TUR as single treatment. Age and treatment in non-teaching hospitals were associated with less adjuvant treatment after TUR. None of the variables sex, age, comorbidity, hospital type, stage and year of treatment was associated with 5 year recurrence or progression rates.